A Pengembangan e-Modul Berbasis Warisan Budaya Untuk Meningkatkan Pemahaman Konsep Siswa - Dhea Safira Nurfitria; Wahyu Henky Irawan (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2026)
The low level of understanding of the concept of circles among vocational school students and the absence of P5/PPRA-based mathematics teaching materials are the basis for this research to develop teaching materials used in the learning process in the form of modules that can be used as learning materials to make them more interesting, varied, and can be studied independently by students outside of class hours. The type of research used in this study was research and development (R&D) with the 4D model (Define, Design, Develop, Disseminate). This research was conducted in class XI of SMK Gajah Mada Mojokerto. The instruments used in this study were interview guidelines, validation sheets, questionnaires, and tests with data collection techniques, namely interviews, written tests, and questionnaires. The data analysis techniques used consisted of validity tests, practicality tests, and effectiveness tests. The validation results show that the e-module meets the validity criteria in terms of language with a percentage of 71.9% and meets the criteria of high validity in terms of material, learning, and IT with percentages of 85.7%, 97.5%, and 97.5%. The results of the practicality test from the questionnaires filled out by teachers yielded a percentage of 86.4%, and from the questionnaires filled out by students, it was 95%, both of which were in the very practical criteria. The results of the effectiveness test obtained from the calculation of pretest and posttest scores with the N-Gain score calculation were 73%, so the e-module is quite effective for use in learning.